PERBEDAAN PENGARUH LATIHAN BOLA VOLI PASSING BAWAH DENGAN TEMAN DAN LATIHAN PASSING BAWAH SENDIRI PADA SISWI KELAS VII SMP NEGERI 24 MERANGIN - Ikhsan Maulana Putra; Refril Dani; Raja Bani Pilitan; Abdulah Abdulah; Megawati Megawati (Jurnal Muara Olahraga, 2023)
Abstract This study aims to find out whether there are differences in underhand passing exercises with friends and underhand passing on the increase in underhand passing in volleyball games for Class VII students of SMP Negeri 24 Merangin. This research is an experimental research with Matched Subject Design. The sample in this study consisted of 20 female students and was divided into experimental group 1 and experimental group 2 using the AB-BA formula. Data analysis in this study used the t-test at a significance level of 5% db 5. Results 1) there is an effect of practicing lower passing alone, with the result of t-count 2.535 > t-table 2.306, 2) there is an effect of practicing lower passing with friends, with a result of t-count 4.482 > t-table 2.306, 3) Training of lower passing with friends are better than the bottom passing exercise alone with a mean post test result of 12.8 > 10.9. The conclusions of the results of this study are 1) There is an effect of lower passing exercises with friends. 2) There is the influence of self-passing exercises. 3) Underhand passing exercises with friends are better than self-passing exercises in improving lower passing abilities in extracurricular students at SMPN 24 Merangin. Keywords: Passing Down, With Friends, Alone